Magnetic hyperthermia-induced drug release from ureasil-PEO-γ-Fe2O3 nanocomposites - Caetano, B. L. [UNESP]; Guibert, C.; Fini, R. [UNESP]; Fresnais, J.; Pulcinelli, S. H. [UNESP]; Ménager, C.; Santilli, C. V. [UNESP] (Royal Society of Chemistry (RSC), 2016)
A multifunctional material suitable for cancer therapy, which combines stimuli-responsive properties for drug delivery and magnetic hyperthermia prepared by a one-pot sol-gel synthesis from the conjugation of ureasil cross-linked poly(ethylene oxide) (U-PEO) hybrid materials with superparamagnetic nanoparticles (γ-Fe2O3), is reported in this communication.